2002
DOI: 10.1143/jjap.41.336
|View full text |Cite
|
Sign up to set email alerts
|

Positive DC Corona Discharge in N2–NO–CO2–O2Mixtures

Abstract: Positive DC corona discharge in a hemicylindrical discharge reactor was applied to mixtures containing N 2 , NO, O 2 , CO 2 and H 2 O, while an NO x chemiluminescence analyzer and an IR spectrometer were used to evaluate the concentration changes and analyze the products of the process in the discharge chamber. The removal efficiency of 89% for NO and the energy cost of 350 eV/molecule were achieved. Special attention was paid to the influence of CO 2 on discharge, its character, performance and products of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The admission of about 5% carbon dioxide into the source gases may quench some processes which inhibit efficient charge exchange of the analyte PAHs in the corona discharge. Others have noted interesting, but unexplained, effects of introducing varying amounts of carbon dioxide with nitrogen into a corona discharge [11]. For example, combinations of nitrogen and carbon dioxide could produce reactive species, which are not present when either gas is used alone, such as ⅐NCO [11].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The admission of about 5% carbon dioxide into the source gases may quench some processes which inhibit efficient charge exchange of the analyte PAHs in the corona discharge. Others have noted interesting, but unexplained, effects of introducing varying amounts of carbon dioxide with nitrogen into a corona discharge [11]. For example, combinations of nitrogen and carbon dioxide could produce reactive species, which are not present when either gas is used alone, such as ⅐NCO [11].…”
Section: Resultsmentioning
confidence: 99%
“…Others have noted interesting, but unexplained, effects of introducing varying amounts of carbon dioxide with nitrogen into a corona discharge [11]. For example, combinations of nitrogen and carbon dioxide could produce reactive species, which are not present when either gas is used alone, such as ⅐NCO [11]. It has also been suggested that carbon dioxide can be decomposed in a corona discharge into carbon monoxide and atomic oxygen [12].…”
Section: Resultsmentioning
confidence: 99%
“…3,4 Corona discharges are useful for environmental applications such as the elimination of NOx and SOx from flue discharges [1][2][3][4][5][6][7] and in industrial uses such as spark switch triggering. [8][9][10][11][12] The corona discharge phenomenon also plays important roles relating to the attachment 13, 14 of downward and upward leaders 13,14 and the reduction in the electric fields near the ground during lightning discharges.…”
Section: Introductionmentioning
confidence: 99%
“…Aritoshi et al investigated the effect of percent-level CO 2 concentration on the NO x conversion and found that the NO x reducing ability is markedly decreased with a 10% CO 2 concentration. Yan et al, Gasparik et al, and Hensel et al investigated the effect of CO 2 added to NO/O 2 /N 2 gas mixtures and found that NO removal was promoted because the type of discharge changed from glow to streamer as the CO 2 concentration increased. Under streamer discharge conditions, the consistent conclusion is that CO 2 inhibits NO x conversion.…”
Section: Introductionmentioning
confidence: 99%